Policy actors and policy making for better migrant health in China: From a policy network perspective - Yapeng Zhu; Kinglun Ngok; Wenmin Li (United Nations Research Institute for Social Development (UNRISD), 2014)
Given the phenomenal scale of internal migration in China, migrant health has become a prominent policy issue. Various policy actors are now involved in the development of migrant health policy. However, little is known about who the main policy actors are, what roles they play, how they interact with each other, and how they might improve their collaboration for better migrant health. This paper aims to identify the main policy actors and explore their roles in migrant health policy making. Applying a "policy network" approach, it finds that the marginalization of migrants in terms of health benefits is mainly attributed to a closed policy network resulting from the peculiar political structure and specific institutional arrangements. Based on these findings, the authors argue that an inclusive policy network is needed to overcome the major institutional barriers and better satisfy migrants health needs.
Keywords: 330